The Relationship Between Quality of Work Life, Job Satisfaction and Burnout in Iranian Occupational Therapists - Amirhossein Dalvand; Samaneh Heidari; Mohammad Kamali; Malahat Akbarfahimi (Function and Disability Journal)
Background and Objectives: Quality of work life (QWL), job satisfaction, and burnout are key factors affecting the professional health of occupational therapists. This study aimed to explore these relationships and the impact of demographic variables on these factors among Iranian occupational therapists. Methods: This cross-sectional analytical study was conducted with 381 Iranian occupational therapists. Data were collected using standard questionnaires and analyzed using Pearson’s correlation tests and multiple linear regression analysis. Results: The Mean±SD scores for QWL were 1.79±1.12; for job satisfaction, 1.7±0.2; and for burnout, 0.24±0.7. Income had a positive and significant relationship with the QWL (β=0.143, P=0.024), career satisfaction (β=0.143, P=0.024), control at work (CAW) (β=0.157, P=0.013), and working conditions (WCS) (β=0.147, P=0.021). Gender was significantly related to job stress (β=0.125, P=0.033) and depersonalization (β=0.259, P<0.001). Increased age was associated with lower intrinsic (β=-0.292, P=0.018) and extrinsic satisfaction (β=-0.261, P=0.038). Other demographic factors, such as education level and marital status, did not significantly affect these indicators. Conclusion: The results suggest that demographic variables, particularly income and gender, significantly predict the QWL and related indicators. Gender-specific support policies and income increases can enhance job satisfaction and reduce burnout among occupational therapists.